Práticas de leitura e escrita na segunda fase do Ensino Fundamental - Nascimento, Carlos Valmir do (2015)
The school as an organized social institution has failed in two very important functions for the literate societies: the formation of proficient readers, and the expansion of discursive competence and language of the students in order to become good producers of written texts, taking into account the genres most commonly used in the social environment. The acts of reading and writing, as well as express exclusively human actions are interactive activities, involve a dialogue between the subjects participating in a communicative process. The importance of reading and writing is related to the social functions that individuals establish and the many benefits they provided. This work was based on conceptions of Solé (1998), Martins (1994), Gotlib (2006), Lajolo and Zilberman (2007), Koch (1994), Kleiman (2002), Gancho (2010), Antunes (2009) and Marcuschi (2008), among others, and aims to analyze the practices of reading and writing from the genre tale, in a class of 9th year of elementary school in a public school and evaluate the effects of these practices on student learning. To this end, we developed a qualitative-quantitative research under the assumption that methodological procedures based on a teaching sequence involving theory and practical activities, implemented through a workshop, enabling students to expand its knowledge of the genre tale, and instruct them regarding the written production that referred to gender and expand their reading possibilities. Therefore, as methodological procedures, we conducted an interview with the students through the application of a questionnaire to check their reading practices and request the production of a story without intervention. Upon completion of the analysis of texts written by the students, we put in place an intervention process through a didactic sequence based on the mistakes they committed in relation to the characteristic structural features of the requested gender, the textuality factors and suitability failures linguistics. At the end of the activities, the students produced a new tale, whose analysis revealed positive results, since the majority of learners overcome the problems committed in the initial production and expanded their communicative competence, which proves the importance of working the reading and writing in elementary school, in the context of genres, adopting an educational sociointeractionist design.